The sins of the father [large type] - Archer, Jeffrey, 1940- (Archer, Jeffrey, 1940- Clifton chronicles, 2012)
Only days before Britain declares war on Germany, Harry Clifton, escaping the consequences of long-buried family secrets and forced to accept that he'll never marry the woman he desires, joins the Merchant Navy. But his ship is sunk in the Atlantic by a German U-boat. An American cruise liner rescues a handful of sailors, among them Harry and an American who dies in the night, providing Harry the chance to escape his tangled past.